Positioning and Navigation Using IMUs and Low-Cost Sensors - Patrick Grates (IEEE Open Journal of Instrumentation and Measurement)
It is possible to supplement consumer navigation systems that are based solely on global navigation satellite system (GNSS) with inertial or magnetic field-based sensors so that an accurate navigation solution can be reached during periods of global positioning system (GPS) denial. A fresh approach uses multiple inertial measurement units (IMUs), three spinning and one unspun, as well as navigation aids for a comprehensive navigation solution. Odometry and magnetometry data is readily available in two thirds of vehicles manufactured after 2018, and this data may be used in conjunction with independent sensors, such as Bluetooth low-energy (BLE) capable digital compasses. IMUs must be rotated in a controlled fashion and filtered to account for bias and data noise. Frequent calibration is required to manage bias stability. This article demonstrates that a reasonable navigation solution can be arrived at during periods of GPS denial of up to 20 min at highway speeds using multiple IMUs and supplementary sensors.